A Series of RET Fusion Spitz Neoplasms With Plaque-Like Silhouette and Dyscohesive Nesting of Epithelioid Melanocytes. (April 2021) - Kim, Daniel; Compres, Elsy V.; Zhang, Bin; Khan, Ayesha U.; Sunshine, Joel C.; Quan, Victor L.; Gerami, Pedram
Abstract : Abstract: Two distinct studies have shown that RET fusions are found in 3%–4% of Spitz neoplasms. RET fusions have been well described in papillary thyroid cancer, non–small-cell lung cancer, breast cancer, and soft-tissue mesenchymal tumors as well as some other neoplasms. However, there are no comprehensive descriptions to date of the characteristic morphologic, clinical, or genomic findings in RET fusion Spitz neoplasms. In this study, we identified 5 cases of RET fusion Spitz neoplasms. These tumors showed characteristic morphologic features which included plaque-like silhouette and monotonous epithelioid cytology with expansile and dyscohesive nesting. Four of 5 patients including 1 diagnosed as Spitz melanoma had clinical follow-up all of which was uneventful. Furthermore, we describe the genomic sequences in 4 of these cases, 2 of which have previously described KIF5B-RET fusion and 2 of which had a novel LMNA-RET fusion. We believe this report significantly contributes to our current knowledge regarding Spitz neoplasms and describes characteristics features which can help with recognition of the RET subgroup of Spitz.